A Prototype of a Queueing Management System using Radxa Rock in Baleendah Public Health Center, Bandung - Siregar, Simon; Ikhsan Sani, Muhammad (School of Applied Science, Telkom University, 2017)
Public Health Center is one of governments' facilities for society that always needs to be improved so it can serve the society with maximum performance to keep the society's health quality good. Queue system at public health center that not perform maximally can caused the public health center's perform ineffectively. In this study, a system consists of a single Board Computer (Radxa Rock), an object oriented programming, Gambas, and a module of a queuing systemis proposed. This system works as a display and voice calling audio module, and a trigger switching module. The outcome of this research for design and implementation of patient's queue number display and voice calling audio system, button system for employee/doctor, communication protocol between button and server have run accordance the proposed design.